Managing a big crisis at Hitachi Electronic Devices (M) Sdn. Bhd. - Hanapiah, Mohd. Faisal (Faculty of Management and Human Resource Development, 2003)
Globalisation has opened up new business opportunities to companies and corporate organizations worldwide. Along with opportunities created, this also means that companies are facing a much higher level of challenges and competitions both from local counterparts and overseas. Challenges come in the form of a crisis. Thus, managing a corporate crisis is crucial because companies need to identify ways and to embrace change management as the consequence of a crisis situation. More importantly, a crisis needs to be handled efficiently through a proper corporate communication approach, since a company's image and reputation is at stake, in order to survive in the fast changing new world economy. This paper analyzes the practice of Hitachi Electronic Devices (M) SOO. Bhd. In dealing with a real crisis from corporate communication perspective.